2022
DOI: 10.30769/usbd.1078434
|View full text |Cite
|
Sign up to set email alerts
|

Covid 19 Döneminde Üniversite Öğrencilerinin Sağlıklı Beslenme Tutum Puanlarının İncelenmesi

Abstract: Bu çalışmanın amacı Niğde Ömer Halisdemir Üniversitesinde okuyan üniversite öğrencilerinin sağlıklı beslenmeye ilişkin tutum ölçeği puanlarının incelenmesidir. Çalışmaya Spor Bilimleri Fakültesinde 334, Sosyal Bilimler 89, Fen Edebiyat Fakültesinde 498 öğrenim gören toplam 921 öğrenci gönüllü olarak katılmıştır. İkili karşılaştırmalarda Independent T testi, gruplar arası farkın belirlenmesinde ise One Way ANOVA testi kullanılmıştır. Analiz sonucunda erkeklerin puan ortalamaları 69,06 olarak belirlenirken kadın… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…This trend was also observed in various studies involving university students, demonstrating that those who partook in regular physical activity generally displayed more favorable attitudes towards healthy nutrition (Arı & Çakır, 2021). Moreover, Yılmaz et al (2022) conducted a study focusing on healthy nutrition attitudes among university students and found a significant difference based on the frequency of physical activity. Students who exercised daily exhibited more positive attitudes towards healthy nutrition.…”
Section: Discussionsupporting
confidence: 64%
“…This trend was also observed in various studies involving university students, demonstrating that those who partook in regular physical activity generally displayed more favorable attitudes towards healthy nutrition (Arı & Çakır, 2021). Moreover, Yılmaz et al (2022) conducted a study focusing on healthy nutrition attitudes among university students and found a significant difference based on the frequency of physical activity. Students who exercised daily exhibited more positive attitudes towards healthy nutrition.…”
Section: Discussionsupporting
confidence: 64%
“…Fakat erkeklerin sağlıklı beslenmeye yönelik ortalamasının kadınlara göre daha fazla olduğunu tespit etmişlerdir. 11 Şahin (2023), muay thai sporcuları üzerine bir araştırma yapmıştır. Araştırmanın cinsiyet değişkeni ile beslenme tutum ölçeği arasında anlamlı bir farklılık bulamamıştır.…”
Section: çAlışma Içinunclassified
“…Bu farklılığın her gün düzenli spor aktivitesi yapan ve düzenli spor alışkanlığı olan kişilerden kaynaklandığını belirtmiştir. 11 Mor ve arkadaşları (2018), spor lisesi öğrencilerinin beslenme alışkanlıklarını incelemişlerdir.…”
Section: çAlışma Içinunclassified
“…For this reason, one of the most basic requirements for a healthy body is nutrition (Sacko and Arslan, 2022;Küçük, 2019). Nutrition is the state of consuming the nutrients required for the body at optimum levels in order to maintain the life functions of the individual since birth and to ensure growth and development (Yılmaz et al, 2022;Yılmaz et al, 2021). It is very important for individuals to consume sufficient and balanced macro and micronutrients in order to have a strong immune system and to be protected against diseases (Süel et al, 2021;Süel et al, 2006).…”
Section: Extended English Summarymentioning
confidence: 99%